THE INFLUENCE OF THE TYPE OF CHOCOLATE ON THE CHEMICAL AND SENSORY CHARACTERISTICS OF MELTED BANANA CHIPS - Sari, Diah Puspita; Lestari, Oke Anandika; Hartanti, Lucky (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2024)
Banana chips are a snack made from thinly sliced bananas that are fried until dry and crispy. Banana chips can be made from various types of bananas and served in a variety of flavors. Banana chips have various types of flavors such as original, sweet, spicy and salty. One popular variation of sweet banana chips is chocolate melted banana chips. Based on survey results, various types of dark chocolate compound brands in circulation have different levels of cocoa powder, namely 8%, 13.5%, and 18.5%. The aim of this research is to obtain the chocolate content that provides the best chemical and sensory characteristics of melted banana chips. The research design used was a Randomized Block Design (RAK) with one factor, namely various types of chocolate content in melted banana chips (C) with 3 treatments, namely: 8% chocolate content (low), 13.5% chocolate content (medium) and chocolate content 18.5% (high). The results obtained by chocolate with a cocoa powder content of 8% (low) had the best physicochemical and sensory characteristics with a water content of 0.65%, ash content of 1.15%, fat content of 30.06%. The color of the melted banana chips is dark brown, has a chocolate aroma, the texture is crisper, and has a sweeter taste.